diff --git a/theories/fin_maps.v b/theories/fin_maps.v index 9ba1fb342b39d50a95b13ea9902103ba7fc42c20..63daffbed3e182560076ff75a0192aa19de86408 100644 --- a/theories/fin_maps.v +++ b/theories/fin_maps.v @@ -1250,6 +1250,9 @@ Lemma insert_merge (m1 : M A) (m2 : M B) i x y z : f (Some y) (Some z) = Some x → <[i:=x]>(merge f m1 m2) = merge f (<[i:=y]>m1) (<[i:=z]>m2). Proof. by intros; apply partial_alter_merge. Qed. +Lemma delete_merge (m1 : M A) (m2 : M B) i : + delete i (merge f m1 m2) = merge f (delete i m1) (delete i m2). +Proof. by intros; apply partial_alter_merge. Qed. Lemma merge_singleton i x y z : f (Some y) (Some z) = Some x → merge f ({[i := y]} : M A) ({[i := z]} : M B) = {[i := x]}. @@ -1280,6 +1283,9 @@ Proof. unfold map_zip_with. by rewrite merge_empty by done. Qed. Lemma map_insert_zip_with {A B C} (f : A → B → C) (m1 : M A) (m2 : M B) i y z : <[i:=f y z]>(map_zip_with f m1 m2) = map_zip_with f (<[i:=y]>m1) (<[i:=z]>m2). Proof. unfold map_zip_with. by erewrite insert_merge by done. Qed. +Lemma map_delete_zip_with {A B C} (f : A → B → C) (m1 : M A) (m2 : M B) i : + delete i (map_zip_with f m1 m2) = map_zip_with f (delete i m1) (delete i m2). +Proof. unfold map_zip_with. by rewrite delete_merge. Qed. Lemma map_zip_with_singleton {A B C} (f : A → B → C) i x y : map_zip_with f ({[ i := x ]} : M A) ({[ i := y ]} : M B) = {[ i := f x y ]}. Proof. unfold map_zip_with. by erewrite merge_singleton. Qed.